2023
DOI: 10.1038/s41598-023-31176-9
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and excretion dynamics of microplastics by black soldier fly larvae and correlation with mouth opening size

Abstract: Black soldier fly (BSF) larvae (Hermetia illucens) are voracious feeders that can be reared on food waste streams originating from the food industry and retailers. Because these food waste streams are automatically being unpacked in substantial amounts, they can contain microplastics, potentially jeopardising the larvae’s chemical safety when applied as compound feed ingredients. During this study, the dynamics of ingestion and excretion of microplastics by BSF larvae reared on substrates containing different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
4
10
1
Order By: Relevance
“…However, when comparing the T1 and T2 larval gut, no MP accumulation over time is detectable. This is also in line with the study of [23], who showed that BSFL ingest and defecate MPs together with the feeding substrate. Unfortunately, the guts of BSFL at T3 were too fragile and the extraction of an entire gut and its content was not feasible.…”
Section: Histology and Microplastic Ingestionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, when comparing the T1 and T2 larval gut, no MP accumulation over time is detectable. This is also in line with the study of [23], who showed that BSFL ingest and defecate MPs together with the feeding substrate. Unfortunately, the guts of BSFL at T3 were too fragile and the extraction of an entire gut and its content was not feasible.…”
Section: Histology and Microplastic Ingestionsupporting
confidence: 91%
“…The average mortality was lowest for PA (9.4% ± 6.3) and highest for PLA (14.9% ± 3.7). Other studies showed similar results, where the Control was compared to MP treatment [13,21,23]. With 33% ± 4.3 and 32% ± 4.4 average pupation rates and 7 ± 1.7 and 7 ± 1.7 days until the rst pupation, respectively, PLA and PA treatments showed similar performance.…”
Section: Larval Developmentsupporting
confidence: 55%
See 2 more Smart Citations
“…Organic wastes suitable as rearing substrate are prone to be contaminated with microplastics. While first studies suggest that the development of farmed insects is not significantly affected by microplastics, these particles are excreted in their original form after passing through the larvae’s digestive tract and accumulate in the frass (Heussler et al, 2023; Lievens et al, 2023). Temperatures exceeding 60 °C have been shown to melt or clump specific microplastics, and temperatures nearing 100 °C might even lead to their elimination (Munno et al, 2018).…”
Section: Discussionmentioning
confidence: 99%